Youth Unemployment and Macroeconomic Determinants in Malaysia - Ma’in, Masturan; Isa, Siti Sarah Mat; Mustaza, Nur Fatihah Nabilah; Johanis, Nur Aina Athirah Mohd (Advances in Social Sciences Research Journal, 2024)
As youth unemployment has been gradually increasing over the years, it is crucial to investigate which economic indicators that significantly contributed in affecting the Malaysia’s youth unemployment rate. In this study, 30 annual data observations from 1991 until 2020 were used to investigate the empirical relationship between youth unemployment rate (YUR) and gross domestic product (GDP), foreign direct investment (FDI), inflation rate (INFR), gross domestic savings (GDS) and trade (TRD) through multiple linear regression analysis using the ordinary least square method. It is hypothesised that these selected macroeconomic determinants have an effect in influencing the Malaysia’s unemployment amongst youth. The results showed that there is positive significant relationship between youth unemployment rate and trade. Whereas, negative significant relationship was found between youth unemployment rate and the GDP as well as GDS. In contrary, there is no significant relationship exists between YUR with FDI and inflation rate.